Increasing consumption vegetables among kids - a matter of attitude and upbringing / Intan Eida Syafinas Mohamed Nasir - Mohamed Nasir, Intan Eida Syafinas (2014)
Eating healthy food is very important to our body, but nowadays many people doesn 't really care and living with unhealthy eating habits. Vegetables are good for our body. Kids, in particular, are reluctant to eat vegetables. It looks like the nature is playing an offensive trick to parents who have kids that hate healthy eating. Why does is happen? Why do kids hate to eat healthy food? What can parents do to avoid this? Every kid loves to eat junk food, sweet, chocolate, fast food because of the attractive advertisement which stimulate them to buy it when they do not even know whether the food is good for them or not. Healthy eating habits can help kids lose weight and avoid childhood obesity and are important to learn at a young age. Today, we can see that not only adults are exposed with the health problem such as obesity. Kids were also having this kind of health problem and this is due to their unhealthy eating styles. Malaysia recorded the highest number of obesity cases in Asean. Utusan Malaysia stated that, Malaysia is number one in Obesity cases. •